Online Learning Model and Assistance of Parents and Private Teachers in Increasing Student Learning Achievement at MIMA KH. Shiddiq Jember - Ahmad Halid (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2024)
This article discusses the online learning model and the assistance of parents and private teachers in improving student learning achievement at MIMA KH. Siddiq Jember. Online learning is not only due to an epidemic, but the demands of contemporary educational developments which require using online. This research uses qualitative methods and data collection uses observation and interviews. The results of this research show that parents and private teachers play a very active role in improving student achievement because there is close cooperation between the school and parents or private teachers at home. So that it can build a learning environment that can encourage students to be active and really learn, and can also help educate students to catch up on lessons they have missed at school.